PENGEMBANGAN BAHAN AJAR KIMIA LARUTAN PADA SEMESTER 2 JURUSAN PMIPA FKIP UNBARI JAMBI - Hasan Basri Said (Jurnal Ilmiah Dikdaya, 2017)
Abstract: Development of teaching materials Chemical solution with contextual learning for FKIP UNBARI Jambi PMIPA department is based on the fact the unavailability of teaching materials especially those that have spesipikasi with contextual learning. This development aims to produce teaching materials Chemical solution with contextual learning for PMIPA department FKIP UNBARI Jambi as grip material faculty and students. Where the research performed at the Department of Guidance and Counseling PMIPA UNBARI Jambi. Product validation teaching materials in this study is a matter experts and instructional media experts, field trials .uji student groups. Teaching materials development activities carried out four (4) phases, (1) the preliminary stage, (2) the stage of development, (3) the stage of preparation of teaching materials products, (4) the stage of expert validation and testing stage products of small groups and large groups. Results of expert validation and expert validation meteri media only give suggestions for the improvement of teaching materials chemical solution. Teaching materials that have been tested in this final group of small and large groups. Results of testing the effectiveness of teaching materials components were analyzed using percentages show good results with an average value of 85.32% dan79,19%. Based on trial results, we can conclude that the solution chemistry teaching materials developed can be used in basic chemistry lectures on the subject of chemical solution.Keywords: Development of Teaching Material Chemical Solution